Comparative analysis of traditional and automated financial management methods - E. A. Frolov (Путеводитель предпринимателя)
The article examines the problems of using traditional and automated methods of financial management, the relevance of which is due to the rapid digital transformation, which creates the need to rethink the methodological foundations. In science, there is a contradiction between established classical management practices and new capabilities of automated systems, which creates uncertainty when choosing optimal approaches to the organization of financial processes. The purpose of the study is to conduct a comprehensive comparative analysis of the management methods under consideration based on a system of criteria (methodology for processing financial information, time characteristics of accounting processes, structure of information flows, mechanisms for controlling operations, principles of reporting, organization of analytical accounting, decision–making procedures, data integration, system scalability, documentation support). The author’s vision of the advantages, disadvantages and limitations of classical options and automation is formulated. It was possible to conclude that the fundamental differences between the characterized methods are determined not only by technological potential, but also by fundamentally different approaches to the organization of information processes. At the same time, the identified differences do not exclude the possibility of methodological integration, provided that the basic principles of financial management are preserved. The presented materials are of practical value to the heads of financial departments, accounting process methodologists, developers of automated management systems.